Difficulties That Students Face During Factorization Questions - Burhanzade, Hulya; Aygor, Nilgun (ELSEVIER SCIENCE BV, 2015)
The purpose of this study is to determine and create a solution to students whom having difficulties at the stage of factorization while solving math questions. The study was qualitative in nature. Samples of the research are 20 students from 3 different private courses in 12th grade, in the 2012-2013 education years in Esenyurt Kirac Rekor, Bahcelievler Netfen and Eyup Bilgem. The data of the research has been gathered by application of the determinant questions of the previous years' University Entrance Exam (OSS) and the course books to the students. The private courses that select for the research are three different private courses in Istanbul with lower income of families. To gather the information of the research 6 questions given to the students that will be answered in classical methods. Results analyzed by the researchers. As a result of the study, it has been seen that the students have major inadequate of the math's fundamentals the Factorization and therefore they were not able to reach the conclusion although they knew the solution. Some of the students could not think to necessary that simplify with factorization in the question. Another part of the students could not realise that they should factorize by utilizing identities. It has been seen that the students are having major lack of knowledge in the fundamentals of mathematics. The reason of this knowledge deficiency based on students who are not solving enough amounts of questions therefore they cannot see the common factors. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Mathematics education; Student Selection Examination(LYS); secondary school mathematics; factorization; Education & Educational Research